LCA of Stage Performances - Life Cycle Assessment of an Opera and a Theatre Stage Performance - Tengström, Johan; Izurieta, Francisco (My University, 2010)
Traditionally are LCA studies carried out for products, but in this project is the LCA methodology used to analyze services. The goal of this study is to investigate the environmental impact from a stage performance in the Göteborg Opera and a stage performance in the Regionteater Väst. The project is divided into several minor LCA studies. The first is an accounting LCA study; one part is for the Regionteater Väst and one part is for the Göteborg Opera. The specific question the LCA study answers is what contributes most to the environmental impact in the Regionteater Väst and the Göteborg Opera. The results, presented by categories, for Regionteater Väst show that building services, transports and materials have the largest emissions. They are 2 kg CO2 eqv/one sold ticket, 3 kg CO2 eqv/one sold ticket and 1.5 kg CO2 eqv/one sold ticket respectively. In the same way, the results for the Göteborg Opera show that building services contribute with, 3kg CO2 eqv/one sold ticket, the transport with 1.7 kg CO2 eqv /one sold ticket and the materials with 6 kg CO2 eqv/one sold ticket. A comparative LCA study is done from a consumer scenario; consume a stage performance in the Regionteater Väst or in the Göteborg Opera. The results shows that it is better to consume a stage performance in the Regionteater Väst compared to the Göteborg Opera from an environmental point of view. The total emission from the Regionteater Väst is 9.4 kg CO2 eqv/one sold ticket and for the Göteborg Opera it is 15.3 kg CO2 eqv/one sold ticket. A comparative LCA study is done of what is worst for the environment; consume a stage performance in the Regionteater Väst/the Göteborg Opera or a T-shirt. From the results is it possible to understand what and why is worst for the environment. The emission for the T-shirt is 3.4 kg CO2 eqv/T-shirt inclusive the shopping tour. A variation analysis is carried out. The number of visitors to the stage performances and what type of vehicle they use back and forth are important factors. For example, the CO2 emissions are reduced by 2 kg per one sold ticket for the Regionteater Väst and for the Göteborg Opera when the numbers of visitors increase with 15% instead of decrease with 15%. There are some recommendations. The employees at Regionteater Väst and the Göteborg Opera should use more public transport and reduce the usage of electricity. The Göteborg Opera should reduce the usage of polycarbonate plastic. It is better to visit a stage performance in the Regionteater Väst instead of one in the Göteborg Opera. Finally, to consume a T-shirt is better than visiting a stage performance.
Keywords: Miljöteknik; Environmental engineering